2018
DOI: 10.1002/mawe.201600714
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rheological and mechanical properties of wood flour reinforced polypropylene

Abstract: This study aims to investigate the rheological and mechanical properties of polypropylene when reinforced by wood flour. In the study, wood flour (WF) was added as filling material to polypropylene (PP), and its effects were investigated. The grain size of the wood flour was 300 mm. Wood flour was mixed into polypropylene material at different rates of weight. Viscosity changes of the polypropylene at various temperatures and pressure values of the concentration rates were documented. As a result, viscosity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mazzanti et al [14] also investigated the influence of temperature and filler concentration on the rheology of wood fiber filled poly(lactic acid) to validate the program for predicting the complex viscosity of the composites at any temperature and filler amount. Altug et al [15] investigated the rheological and mechanical properties of poly-propylene reinforced with wood fiber. Studies have shown that the flow property reduces depending on the reinforcement wood fiber content added to the reinforced plastics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazzanti et al [14] also investigated the influence of temperature and filler concentration on the rheology of wood fiber filled poly(lactic acid) to validate the program for predicting the complex viscosity of the composites at any temperature and filler amount. Altug et al [15] investigated the rheological and mechanical properties of poly-propylene reinforced with wood fiber. Studies have shown that the flow property reduces depending on the reinforcement wood fiber content added to the reinforced plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the flow property reduces depending on the reinforcement wood fiber content added to the reinforced plastics. The amount of wood fiber added is an important factor affecting the rheological properties of WPCs [7,15,16]. The rheological phenomenon caused by high fiber contents, such as a high viscosity, and strong shear thinning behavior, must be understood to properly formulate WPCs.…”
Section: Introductionmentioning
confidence: 99%